Abstract representations of events arise from mental errors in learning and memory - Christopher W. Lynn (Nature Portfolio, 2020)
Humans can easily uncover abstract associations. Here, the authors propose that higher-order associations arise from natural errors in learning and memory. They suggest that mental errors influence the humans’ representation of the world in significant and predictable ways.